Analisis Kandungan Serat pada Snack Bar Substitusi Tepung Bekatul dan Tepung Jamur Tiram Putih - Siti Luqiyatun Ni’mah; Lilia Faridatul Fauziah (Yayasan Literasi Sains Indonesia, 2024)
Obesity is a complex disease characterized by excessive fat accumulation in the body. Obesity is caused by an imbalance between the amount of energy intake and energy expenditure. To provide additional fiber to adolescents, it is hoped that by making a snack bar substitution of bran flour and white oyster mushroom flour, it can be used as an alternative high-fiber snack for adolescents. The purpose of this study was to determine the effect of substitution of rice bran flour and white oyster mushroom flour on fiber content in snack bars. His type of research used True Experimental with Completely Randomized Design (CRD) with 4 levels of treatment and 6 replications. The treatment carried out was by comparing the proportion of wheat flour: rice bran flour: white oyster mushroom flour in each P0 (100:0:0), P1 (0:70:30), P2 (0:30:70), P3 (0:50:50). The results showed that there was an effect of increasing fiber content in snack bars, the more rice bran flour was added, the fiber content increased, with the highest fiber content in treatment P3, which was 8.06 gr. There was a tendency for the addition of rice bran flour, the more rice bran flour and white oyster mushroom flour were added, the fiber content in snack bars increased.